(untitled) (European Journal of Pure and Applied Mathematics, 2010)
In this paper we defined the double infinite matrix A = a(m, n, k) and study the action of A on fÂ is inÂ L^2(R) and on its prolate spheroidal wavelet coefficients. We also find the frame condition for A-transform of fÂ isÂ inÂ L^2(R) whose wavelet series expansion is known.